Application of single-station sigma and site-response characterization in a probabilistic seismic-hazard analysis for a new nuclear site - Rodriguez-Marek,A; Rathje,EM; Bommer,JJ; Scherbaum,F; Stafford,PJ (Bulletin of the Seismological Society of America, 2014)
Aleatory variability in groundmotion prediction, represented by the standard deviation (sigma) of a groundmotion prediction equation, exerts a very strong influence on the results of probabilistic seismichazard analysis (PSHA). This is especially so at the low annual exceedance frequencies considered for nuclear facilities; in these cases, even small reductions in sigma can have a marked effect on the hazard estimates. Proper separation and quantification of aleatory variability and epistemic uncertainty can lead to defensible reductions in sigma. One such approach is the singlestation sigma concept, which removes that part of sigma corresponding to repeatable sitespecific effects. However, the sitetosite component must then be constrained by sitespecific measurements or else modeled as epistemic uncertainty and incorporated into the modeling of site effects. The practical application of the singlestation sigma concept, including the characterization of the dynamic properties of the site and the incorporation of siteresponse effects into the hazard calculations, is illustrated for a PSHA conducted at a rock site under consideration for the potential construction of a nuclear power plant.